Modeling and testing of a nano-satellite and implementation of a BalloonSat with data analysis - Shafique, Ishraque Bin; Rabbi, Fazle; Halim, Razzaq; Mahmood, Arik (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.